(3GdefGgds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
(3ChdgG(B: (3eG PcQGg ChdG JUQjM cKjQ HGSJMHGH GdhVhA dUdGI GdfGadI hKGfjG OYhi dGLeGY Ydi GSJMHGHg dgG aj UQjM HYV TQhM GdLYaQjIs
(3BNQgG (B:s
(3BNQgG(B: (3hgd jLH HYO ZSd GdEfGA ef GdfLGSI Ydi GdhLg GdeYJHQ TQYG JLajag, ChdG UQM HGdKGfj aj GdJMQjQ hGdHjGf (B.. (3jXgQ GdChd ef GdebfYI hgh VYja EdG EPG CQGO ef GdJLaja ERGdI GdZSGdI GdfLSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B22: 221s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis